APACHE II score validation in emergency abdominal surgery. A post hoc analysis of the InCare trial. Issue 2 (14th October 2019) - Hansted, Anna K.; Møller, Morten H.; Møller, Ann M.; Vester‐Andersen, Morten
Abstract : Background: Patients undergoing emergency abdominal surgery are at high risk of morbidity and mortality. Accurate identification of high‐risk patients is important. The Acute Physiology and Chronic Health Evaluation (APACHE) II score needs to be validated in a larger heterogeneous population before implementation. We aimed to assess the predictive value of the APACHE II score in emergency abdominal surgical patients. Furthermore, we compared the APACHE II score with the American Society of Anesthesiologists (ASA) physical status score and the Charlson Comorbidity Index (CCI). Methods: We included adult patients undergoing emergency abdominal surgery screened for enrolment in the InCare trial from October 2010 to November 2012. The APACHE II score was evaluated with area under the receiver operating characteristics curve (AUROC) statistics. The primary outcome was 30‐day mortality. Secondary outcomes included 90‐day mortality and admission to the intensive care unit. Results: We included a total of 885 patients. All‐cause 30‐day mortality was 5.0%, 90‐day mortality was 8.9%, and a total of 7.9% of the patients were admitted to the intensive care unit. The AUROC (95% confidence interval) of the APACHE II score was 0.72 (0.65‐0.80) for 30‐day mortality, 0.70 (0.64‐0.76) for 90‐day mortality and 0.65 (0.59‐0.71) for admission to the intensive care unit. The CCI performed better in prediction of 90‐day mortality ( P  = .04). All other results for the ASA score and CCI were comparable with the APACHE II score. Conclusion: The APACHE II score predicted mortality moderately and admission to intensive care unit poorly in emergency abdominal surgical patients.